Influence of cold atmospheric plasma of microdischarge on fungal mycelium and spores growing - Veremii, Yu.; Andriiash, I.; Tsvyd, N.; Chernyak, V.; Sukhomlyn, M.; Martysh, Eu. (Вопросы атомной науки и техники, 2019)
The effect of cold plasma microdischarge on the development of spores and mycelium of fungi was investigated. The influence was investigated on Penicilium sp. The results of cold-plasma spores’ treatment showed that it could damage their outer shell and slow the colony growth, as well as stimulate germination of spores. Досліджено вплив холодної плазми мікророзряду на розвиток спор і міцелію грибів. Вплив досліджували на зразках Penicilium sp. Результати обробки спор холодною плазмою показали, що вона може пошкодити їхню зовнішню оболонку і уповільнити розростання колонії, а також стимулювати проростання спор. Исследовано влияние холодной плазмы микроразряда на развитие спор и мицелия грибов. Влияние исследовали на образцах Penicilium sp. Результаты обработки спор холодной плазмой показали, что она может повредить их внешнюю оболочку и замедлить рост колонии, а также стимулировать прорастание спор.